PREVALENCE AND PECULIARITIES OF CONSTIPATION IN CHILDREN IN RUSSIA: POPULATION STUDY - S.I. Erdes; B.O. Matsukatova (Вопросы современной педиатрии, 2010)
Topicality of problem of constipation is conditioned by steady growth of its prevalence in children, and by need of timely revelation of such patients for administration of proper therapy. The objective of this study was evaluation of prevalence and clinical peculiarities of constipation in children taking into account diagnostic criteria of Rome Consensus III. A questionnaire poll of 1,216 children or their parents in Central, North and South Federal Districts of Russian Federation was performed. Patients 1 month — 18 years old participated this study. Frequency of constipation was 59%. The study showed high frequency of functional intestinal disorders: impediment of defecation, prolonged stay in toilet, overflow or swelling of stomach, feeling of incomplete defecation, pathological changes of stool. Spastic component plays significant role in formation of constipation. The frequency of complications of constipation was low. Authors showed frequent presence of functional disorders in children with normal regimen of defecation. Analysis of quality of life was performed. It showed that constipation has an influence on common state of health, usual activity and studying of patients. Authors made a conclusion that present data does not reflect true rate of children’s constipations.Key words: children, functional constipation, prevalence.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):50-56)